Rekomendasi implementasi keberlanjutan agroindustri serat kenaf pada jaringan rantai pasok hulu - Nunung Nurhasanah; Dhia Puti Andini Wibowo; Nita Noriko; Tharra Azzahra Riyana; Syarif Hidayat; Budi Aribowo; Dody Haryadi (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Environmental issues are a priority in the development of the kenaf fiber industry globally, because kenaf fiber is considered an environmentally friendly vegetable fiber when used as a raw material. This is revealed from the retting process which is the main process in processing the kenaf plant into kenaf dry fiber. The purpose of this study was to determine the green productivity index on the upstream side of the kenaf fiber agro-industry network by mapping green value stream mapping. Based on the research that has been done, it can be concluded that there are 6 alternatives to clean production, 4 of which can add value to the waste and 2 of them are routine activities of the kenaf fiber agroindustry. Then the results of the GVSM Current State mapping on energy of 12,753.6 Joules, water as much as 32,810.1l, material as much as 14,340 kg, waste as much as 14,860 kg, emissions of 1,584 kg, and biodiversity as much as 4,000 kg. After the alternative production is carried out, the results of the GVSM Future State mapping are 11,159.4 Joules of energy, 32,810.1l of water, 14,340 kg of materials, 1,584 kg of emissions, and 4,000 kg of biodiversity. There was a reduction in energy in the form of human power of 1,594.2 Joules which was replaced by the use of machines. The GPI Current State value in the kenaf fiber agroindustry is 0.000759 and the GPI Future State value obtained is 0.001234. This means that the production alternatives given affect the increase in IE value and decrease in EI value from the kenaf fiber agroindustry so that the GPI Future State value produced is getting better so that the impact on the environment in the kenaf fiber agroindustry is decreasing.